Diversidade morfológica e genética de rizobactérias endofíticas obtidas de solos de diferentes classes e manejos de cultivo - Neiverth, Walkyria (2012)
Nitrogen is one of the limiting factors of crop production, but its continuous availability by applying chemical fertilizer in agriculture, will lead to high costs, both economic and environmental. To reduce these costs, several studies have been conducted regarding the biological nitrogen fixation (BNF) and use of plant growth-promoting bacteria (PGPB). Considering that the great diversity of soil microorganisms has not been yet catalogued, the goal of this work was to study the morphological and genetic diversity of endophytic rhizobacteria obtained from soils of different classes and crop managements in order to isolate individuals with potential for PGPB. Bacteria were isolated from diluted soils and inoculated in bait-plants of wheat grown in the nutrient solution. After 30 days, the plant tissue was superficially sterilized and macerated and an aliquot of serial dilutions was inoculated in selective medium Dygs with successive plating to obtain pure colonies. Bacterial growth was quantified by counting colony forming units (c.f.u.) and 400 morphologically distinct colonies were characterized: size, shape, color, edge, homogeneity, transparency, elevation, and mucus. Based on this information, the isolates were analyzed and grouped by using the program Past for morphological typing. From these 269 strains were genetically characterized by rep-PCR with specific primer. Polymorphic profiles obtained were analyzed and grouped with BioNumerics software. Calculations regarding the rates of morpho-genetic diversity and richness were performed by SPADE program. The managements with succession of corn and soybean in organic system (M10) and corn - soybean RR (M8) were the ones showing higher and lower c.f.u, respectively. The great biodiversity found in the various types of soil under different culture managements from evaluated regions have resulted in a total of 35 morphological and 25 genetics groups. As for genetic groups, there was, in addition to the 25 major groups, 16 profiles when used 60% of similarity. In morphological groups, it was observed greater number of profiles relating to riparian forest area (M4), whereas the smallest number was observed in succession corn and organic soybean on zero tillage (M10). It was found higher morphological diversity index, richness and groups expected in future collection management with monoculture of sugar cane, high levels of P in soil and application of vinasse (M1), being the lowest indexes for the monoculture management with sugar cane with low P in soil and mineral fertilization (M2). As for diversity indexes and genetic richness the M1 management stands out as showing the higher diversity indexes, but the highest rates of richness and groups expected in future collection were observed in the succession corn - soybean (M9) management. By contrast, the lowest rates of genetic diversity and richness were appointed by management with organic soybean on zero tillage. The results showed a high diversity in all areas assessed, both for the different cultivation managements, soil types, as to characteristic vegetation of the different areas, pointing the concomitant influence of these agri-environmental characteristics on the dominance of specific morpho-genetic groups within the communities